Cytokinin fluoroprobe reveals multiple sites of cytokinin perception at plasma membrane and endoplasmic reticulum - Kubiasová, Karolina; Montesinos, Juan Carlos; Šamajová, Olga; Nisler, Jaroslav; Mik, Václav; Semerádová, Hana; Plíhalová, Lucie; Novák, Ondřej; Marhavý, Peter; Cavallari, Nicola; Zalabák, David; Berka, Karel; et al. (Nature communications, 2020)
Plant hormone cytokinins are perceived by a subfamily of sensor histidine kinases (HKs), which via a two-component phosphorelay cascade activate transcriptional responses in the nucleus. Subcellular localization of the receptors proposed the endoplasmic reticulum (ER) membrane as a principal cytokinin perception site, while study of cytokinin transport pointed to the plasma membrane (PM)-mediated cytokinin signalling. Here, by detailed monitoring of subcellular localizations of the fluorescently labelled natural cytokinin probe and the receptor ARABIDOPSIS HISTIDINE KINASE 4 (CRE1/AHK4) fused to GFP reporter, we show that pools of the ER-located cytokinin receptors can enter the secretory pathway and reach the PM in cells of the root apical meristem, and the cell plate of dividing meristematic cells. Brefeldin A (BFA) experiments revealed vesicular recycling of the receptor and its accumulation in BFA compartments. We provide a revised view on cytokinin signalling and the possibility of multiple sites of perception at PM and ER.
Keywords: proteiny huseníčku; Endoplasmic Reticulum; Fluorescent Dyes; Recombinant Fusion Proteins; Arabidopsis; signální transdukce; brefeldin A; proteinkinasy; endoplazmatické retikulum; Arabidopsis Proteins; meristém; rekombinantní fúzní proteiny; receptory buněčného povrchu; Cytokinins; Signal Transduction; Meristem; cytokininy; Cell Membrane; Plants, Genetically Modified; zelené fluorescenční proteiny; Brefeldin A; Protein Kinases; buněčná membrána; fluorescenční barviva; Green Fluorescent Proteins; Receptors, Cell Surface; geneticky modifikované rostliny